Robotic thymectomy: a review of techniques and results - Coco, Danilo; Leanza, Silvana (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2023)
Thymectomy is a well-established therapeutic option in the multidisciplinary treatment of nonthymomatous myasthenia gravis (MG) and in thymoma treatment. Although many surgical procedures for thymectomy have been identified, the transsternal method is still regarded as the gold standard. Minimally invasive procedures, on the other hand, have achieved popularity in the last decades and are now extensively used in this field of surgery. Among them, robotic thymectomy has been the most cutting-edge surgical procedure. Several authors and meta-analyses have shown that a minimally invasive approach to thymectomy is associated with improved surgical results and fewer complications in surgery compared to transsternal open thymectomy, without any substantial changes in myasthenia gravis complete rates of remission. Hence, in the present review of the literature, we aimed to describe and delineate the techniques, advantages, outcomes, and future perspectives of robotic thymectomy. Existing evidence suggests that robotic thymectomy will likely become the gold standard for thymectomy in early stage thymomas and MG subjects. Many of the drawbacks related to other minimally invasive procedures appear to be resolved by robotic thymectomy, and long-term neurological outcomes are satisfactory. In addition, improved vision and high dexterity of instrument movements enable safe and complete thymic tissue dissection, superior to standard thoracoscopic procedures. The access with minimally invasive surgery VATS (video-assisted thoracoscopic surgery) or RATS (robot-assisted thoracic surgery) access in its various variants allows the extent of mediastinal fat resection due to the possibility of ectopic thymic foci in the mediastinum determining the long-term outcome in the group of patients operated on for myasthenia gravis. However, it was recommended to carry out better designed, multi-centre, randomized studies to arrive at definitive conclusions on robotic thymectomy for thymomas and myasthenia gravis treatment.